Creating institutional preconditions for knowledge flows in cross-border regions. (March 2018) - Miörner, Johan; Zukauskaite, Elena; Trippl, Michaela; Moodysson, Jerker
In recent years, we have witnessed an intensive scholarly discussion about the limitations of traditional inward looking regional innovation strategies. New policy approaches put more emphasis on promoting the external connectedness of regions. However, the institutional preconditions for collaboration across borders have received little attention so far. The aim of this paper is to investigate both conceptually and empirically how policy network organizations can target the institutional underpinnings and challenges of cross-border integration processes and knowledge flows. The empirical part of the paper consists of an analysis of activities performed by four cross-border policy network organizations in the Öresund region (made up of Zealand in Denmark and Scania in Sweden) and how they relate to the creation of institutional preconditions and the removal of institutional barriers. Our findings suggest that cross-border policy network organizations have limited power to change or facilitate the adaptation of formal institutions directly. They mainly rely on mobilizing actors at other territorial levels for improving the formal institutional conditions for knowledge flows. Informal institutions, on the other hand, can be targeted by an array of different tools available to policy network organizations. We conclude that institutional preconditions in cross-border regions are influenced by collective activities of multiple actors on different territorial levels, and that regional actors mainly adapt to the existing institutional framework rather than change it. For innovation policy, this implies that possibilities for institutional change and adaptation need to be considered in regional innovation policy strategies.